Danggui Sini Decoction Protected Islet Endothelial Cell Survival from Hypoxic Damage via PI3K/Akt/eNOS Pathway. (10th July 2018) - Chen, Wenting; Huang, Caoxin; Yang, Chen; Ge, Xilin; Huang, Wenfang; Li, Xuejun; Yang, Shuyu; Liu, Suhuan
Abstract : Danggui Sini decoction (DSD) is a traditional Chinese decoction, which is wildly applied and showed to be effective in ameliorating ischemia-related symptoms. However, the mechanisms of DSD action in ischemic damage remain to be fully clarified. Pancreatic islet endothelial cells are pivotal constituent of islet microvasculature, with high vulnerability to hypoxic injuries. Here, using MST1 cell, a pancreatic islet endothelial cell-line, as a model, we investigated the effects of DSD on hypoxia-stimulated endothelial cell lesions and its underlying mechanisms. We found that DSD-Containing Serum (DSD-CS), collected from DSD-treated rats, could efficiently protect MST1 survival and proliferation from Cobalt chloride (CoCl2 ) induced damage, including cell viability, proliferation, and tube formation. Furthermore, DSD-CS restored the activity of PI3K/Akt/eNOS signaling inhibited by CoCl2 in MST1 cells. The protective effect of DSD-CS could be blocked by the specific PI3K/Akt/eNOS inhibitor LY294002, suggesting that DSD-CS protection of MST1 cell survival from hypoxia was mediated by PI3K/Akt/eNOS pathway. In conclusion, DSD treatment protected MST1 survival from hypoxic injuries via PI3K/Akt/eNOS pathway, indicating its role in protecting microvascular endothelial cells.